2020
DOI: 10.1007/s11606-020-06222-1
|View full text |Cite
|
Sign up to set email alerts
|

Are Improvements Still Needed to the Modified Hospital Readmissions Reduction Program: a Health and Retirement Study (2000–2014)?

Abstract: BACKGROUND:To address concerns that the Hospital Readmissions Reduction Program (HRRP) unfairly penalized safety net hospitals treating patients with high social and functional risks, Medicare recently modified HRRP to compare hospitals with similar proportions of high-risk, dual-eligible patients ("peer group hospitals"). Whether the change fully accounts for patients' social and functional risks is unknown. OBJECTIVE: Examine risk-standardized readmission rates (RSRRs) and hospital penalties after adding pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…Our analysis also suggested that other safety net definitions may not adequately capture high ACSC hospitals. For instance, although we observed an association between ACSC visits to high ACSC hospitals and to hospitals with the highest quintile of dual-eligible patients, which previous work suggests may serve patients who are particularly vulnerable, [ 23 ] the overall proportion of dual-eligible patients was only weakly correlated with proportion of ACSC visits. Our results also suggest that high ACSC hospitals were less likely to be public hospitals, and more likely to be for-profit hospitals, compared to non-profit hospitals, which may reflect findings from previous studies that geography and market structure may influence service offerings and patient case-mix at hospitals of different ownership [ 32 – 35 ].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Our analysis also suggested that other safety net definitions may not adequately capture high ACSC hospitals. For instance, although we observed an association between ACSC visits to high ACSC hospitals and to hospitals with the highest quintile of dual-eligible patients, which previous work suggests may serve patients who are particularly vulnerable, [ 23 ] the overall proportion of dual-eligible patients was only weakly correlated with proportion of ACSC visits. Our results also suggest that high ACSC hospitals were less likely to be public hospitals, and more likely to be for-profit hospitals, compared to non-profit hospitals, which may reflect findings from previous studies that geography and market structure may influence service offerings and patient case-mix at hospitals of different ownership [ 32 – 35 ].…”
Section: Discussioncontrasting
confidence: 56%
“…The primary predictor of interest was hospital safety net status. Because of the multiple definitions for safety net status, we used three different definitions: (i) hospitals with the highest quartile of the DSH patient percentage; (ii) public hospitals; and (iii) EDs serving the highest quintile of age-eligible Medicare patients with dual-eligibility for Medicare and Medicaid [ 20 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Further, the peer group-based payment adjustment approach was introduced to the HRRP and implemented beginning in 2019. Early evidence shows that peer grouping resulted in relatively lessening the burden of financial penalties serving more socially disadvantaged patients (104)(105)(106)(107). However, the current modification has limitations where it merely reflects on its readmission outcomes and not the social risk factors of its patients, which is the fundamental goal, and it might not be an perfect approach to address health care inequities in the current form (107).…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…In all, the results suggest that the incorporation of fall injuries into evaluations of national policy might benefit older adult welfare. HRRP has been critiqued for its limited impact on quality, 50 , 51 , 52 , 53 leading to calls for its withdrawal as a quality program. 37 , 48 Yet, a more comprehensive evaluation may offer a different portrait, by revealing effects on clinically and socially relevant outcomes involving fall injuries.…”
Section: Discussionmentioning
confidence: 99%